TRANSFORMASI SISTEM AKUAKULTUR MELALUI INTEGRASI TEKNIK GENETIKA DAN BIOTEKNOLOGI - Muhammad Fuad; Risqah Amaliah Kasman (Prosiding Seminar Nasional Indonesia, 2025)
The transformation of aquaculture systems is a strategic need to answer the challenges of increasing demand for animal protein, limited resources, and the threat of diseases in cultivated organisms. This research aims to analyze the role of the integration of genetic engineering and biotechnology in encouraging a change in the cultivation paradigm towards a more efficient, precise, and sustainable system. The research method uses a descriptive qualitative approach through a literature review of scientific publications from the Scopus and ScienceDirect databases for the period 2012–2025. The results of the analysis show that the application of technologies such as genomic selection, marker-assisted selection, and CRISPR/Cas9 gene editing is able to improve superior traits such as rapid growth, feed conversion efficiency, and disease resistance. The integration of molecular biotechnology through 'omics' approaches (genomics, transcriptomics, proteomics) also supports precise monitoring of organism health and data-driven decision-making. However, the main challenges include ethical issues, limited infrastructure, biotechnology literacy, and strict biosafety regulations. In conclusion, aquaculture transformation through genetic and biotechnology synergy has the potential to accelerate the realization of sustainable aquaculture systems, but requires policy support, research investment, and institutional capacity strengthening for optimal implementation.